2022
DOI: 10.1002/pol.20220177
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐highTgand ultra‐low coefficient of thermal expansion polyimide films based on hydrogen bond interaction

Abstract: To tolerate high processing temperature during the fabrication of low-temperature polycrystalline silicon thin-film transistors (LTPS-TFT) in flexible OLED devices, the polyimide (PI) films, which are used as substrate, should have ultra-high glass transition temperature (T g > 450 C) and ultra-low coefficient of thermal expansion (CTE at 0-5 ppm K À1 ). In this paper, two novel heterocyclic monomers, namely, N,N'-(xanthone-2,7-diyl)bis(4-aminobenzamide) (p-DAXBA) and N,N'-(xanthone-2,7-diyl)bis(3-aminobenzami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Intermolecular interaction can be tested by DMA by determining the tan δ value, which reflects the energy loss during motion of the polymeric chain; the larger the tan δ value, the greater the internal friction of the polymeric chain or segments, restricting their movement . In Figure b, it can be seen that the peak of tan δ increased with increasing amount of DAPyBA, which indicated that the co-polymerization of DAPyBA effectively increased intermolecular interactions due to the presence of inter-HBs. , Therefore, we conclude that multiple inter-HBs in co-PIs arising from DAPyBA units increase the interaction between molecules, resulting in closer molecular packing. The smaller chain spacing means that a greater force is required for slippage between molecular chains, such that the tensile strength and initial modulus of the PI are significantly enhanced.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermolecular interaction can be tested by DMA by determining the tan δ value, which reflects the energy loss during motion of the polymeric chain; the larger the tan δ value, the greater the internal friction of the polymeric chain or segments, restricting their movement . In Figure b, it can be seen that the peak of tan δ increased with increasing amount of DAPyBA, which indicated that the co-polymerization of DAPyBA effectively increased intermolecular interactions due to the presence of inter-HBs. , Therefore, we conclude that multiple inter-HBs in co-PIs arising from DAPyBA units increase the interaction between molecules, resulting in closer molecular packing. The smaller chain spacing means that a greater force is required for slippage between molecular chains, such that the tensile strength and initial modulus of the PI are significantly enhanced.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The results show that the co-PI films had good thermal decomposition stability, meeting the needs of the vast majority of applications. However, compared with Kapton PI, co-PIs have slightly lower T d values due to the presence of relatively unstable amide groups containing single bonds. , In order to further understand the thermogravimetric process of PI films, the first-order derivative of the thermal weight loss curve was performed to obtain the thermal weight loss rate curve (DTG), as shown in Figure b. PI-0 had only one thermal weight loss peak, which was located roughly at 550–650 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is generally straightforward to wrap films such as flexible LC cells around uniaxially curved surfaces because no stretching is required. However, in order to take an initially planar flexible LC optical film and wrap it around a biaxially curved surface it must be stretched [1,2]. This paper reports on how TAC-film based active LC optics can be biaxially curved around surfaces while also enabling ambient dimming.…”
Section: Introductionmentioning
confidence: 99%
“…They found that films obtained through polymerization of diamine DAR-4AB containing benzobisoxazazole and rigid dianhydride 2,3,6,7-naphthalenetetracarboxylic dianhydride exhibited excellent thermal properties, including a CTE of 3.3 ppm K À1 and 5% weight-loss temperature (T d5% ) exceeding 600 C. The authors attributed this result to diamine DAR-4AB improving linearity and stiffness of molecule. Jiao et al [37][38][39] prepared a range of PI films with stiff xanthone, T g and CTE of best result were >450 C and 2.7 ppm K À1 , respectively. Yang et al 40 prepared diamines 2,5-bis(4-aminophenyl)pyridine (PRD) and 2,5-bis(4-aminophenyl)pyrimidine (PRM) containing pyridine and pyrimidine structures.…”
Section: Introductionmentioning
confidence: 99%